Influencia del método de inoculación y el encalamiento del suelo de Carimagua (Llanos orientales, Colombia) en la nodulación de leguminosas - Morales, V. M.; Graham, P.H; Cavallo, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
This paper reports inoculation and pelleting studies carried out in highly acid soils of the Llanos Orientales of Colombia. In all plants studied there was a significant response to inoculation. Pelleting of the seed improved nodulation further in Phaseolus vulgaris and Leucaena leucocephala even with 6.0 tons/hectare lime amendment. At low line amendment levels pelleting also improved nodulation in Stylosanthes and in Vigna sinensis. The least satisfatory of the pelleting materials used was Esxcorias Thomas, but there was no significant differences in the results obtained for CaCO3 and rock phosphate. Lime treatment of soil to levels greater than 0.5 tons CaCO3 hactare were not necessary where the seeds were inoculated and pelleted. In Leucaena strain differences were noted in resistance to soil acidity